1972
DOI: 10.1002/ar.1091730403
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro and in vivo study of single palatal processes

Abstract: Single palatal processes were grown in organ culture to test whether epithelial contact was a prerequisite for the cytological alterations observed during midline epithelial disruption. Observations were made with the light and electron microscopes. Palatal processes from 14 day C57BL mice were cultured on Millipore filters and fixed in paraformaldehyde and osmium tetroxide. Fine structure studies of 24 hour cultures revealed a thick basal lamina beneath an intact epithelium. Epithelial cells were absent along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Cell death during palatogenesis has been considered as apoptosis by electron microscopy (BRUSATI, 1969;HAYWARD, 1969, SHAPIRO andSWENEY, 1969;SMILEY, 1972). The present electron microscopic study confirmed that nuclear chromatin condensation and cell shrinkage appear in MEE cells, while apoptotic bodies, which are often phagocytosed by adjacent MEE cells, are present in the medial edge epithelium prior to contact-in some cases in the epithelial seam, and in the epithelial triangles and pearls.…”
Section: Apoptosis Of Mee Cells During the Palatal Formationsupporting
confidence: 74%
See 1 more Smart Citation
“…Cell death during palatogenesis has been considered as apoptosis by electron microscopy (BRUSATI, 1969;HAYWARD, 1969, SHAPIRO andSWENEY, 1969;SMILEY, 1972). The present electron microscopic study confirmed that nuclear chromatin condensation and cell shrinkage appear in MEE cells, while apoptotic bodies, which are often phagocytosed by adjacent MEE cells, are present in the medial edge epithelium prior to contact-in some cases in the epithelial seam, and in the epithelial triangles and pearls.…”
Section: Apoptosis Of Mee Cells During the Palatal Formationsupporting
confidence: 74%
“…MEE cells in the seam are known to contain numerous lysosomes, which are often defined as suicidal bags (POURTOIS, 1966;BRUSATI, 1969;HAYWARD, 1969;SMILEY, 1972). Lysosomes have been shown to participate in the dying process of some embryonic cells by forming 191 autolysosomes (CLARLE, 1990); however, no direct evidence has been reported showing lysosomal participation in palatal formation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the organ-cultured palatal shelf of the rat fetus on day 14 of gestation showed a relatively wide location of the cells with capacity of autolysis [Pratt and Martin, 1975;Smiley and Koch, 1972]. Therefore, the fusing area presumably overlaps with the location where DNA synthesis ceases, and this does not contradict the remodeling concept.…”
Section: Discussionmentioning
confidence: 95%
“…Although palate organ cultures enable various experiments which are impossible in utero, they sometimes produce conflicting results. Palate culture methods reported thus far can be largely divided into the static culture method using a CO 2 incubator (Pourtois, 1966(Pourtois, , 1968Smiley and Koch, 1971, 1972, 1975Dixon and Ferguson, 1992;Griffith and Hay, 1992;Martínez-Álvarez et al, 2000;Cuervo et al, 2002;Cuervo and Covarrubias, 2004) and the suspension culture method with rolling bottles (Shiota et al, 1990;Brown et al, 2002). In those cultures, some fundamental questions remain such as: (1) In order from the left, oral and medial views of the single shelf explants, and the cell morphology of the medial edge and oral and nasal epithelia, respectively.…”
Section: Introductionmentioning
confidence: 99%